Karakteristik Remaja yang Memanfaatkan Layanan Kesehatan Reproduksi Remaja Di Wilayah Kerja Puskesmas Martapura 1 - Annisa Febriana; Sigit Mulyono; Widyatuti Widyatuti (FORIKES, 2020)
Reproductive health is one of the problems that occur in adolescent life. Adolescents who have never been exposed to information about reproductive health from an early age are the main causes of these problems. Reproductive health service facilities for adolescents are available at the Puskesmas, but have not been properly utilized by adolescents. The purpose of this study was to determine the relationship of adolescent characteristics with the utilization of adolescent reproductive health services. The method used is descriptive. The sampling technique used was random sampling, as many as 370 teenagers who had used reproductive health services. Results. There is a relationship of age (p value 0.01), parental past education (p value 0.02), and parental income (p value 0.01) with the use of adolescent reproductive health services. Research recommendations are expected that community nurses can increase the scope of visits both at school and in families with adolescents so that adolescents are more exposed to information about reproductive health and are able to make use of available reproductive health services optimally. Keywords: characteristics; adolescents; reproductive health; utilization of reproductive services ABSTRAK Kesehatan reproduksi menjadi salah satu permasalahan yang terjadi dalam kehidupan remaja. Remaja yang tidak pernah terpapar informasi mengenai kesehatan reproduksi sejak dini menjadi penyebab utama timbulnya masalah tersebut. Fasilitas layanan kesehatan reproduksi untuk remaja telah tersedia di Puskesmas, namun belum dimanfaatkan dengan baik oleh remaja. Tujuan penelitian untuk mengetahui hubungan karakteristik remaja dengan pemanfaatan layanan kesehatan reproduksi remaja. Metode yang digunakan adalah deskriftif. Teknik pengambilan sampel yang digunakan adalah random sampling, sebanyak 370 remaja yang pernah memanfaatkan layanan kesehatan reproduksi. Hasil. Terdapat hubungan usia (p value 0,01), pendidikan terakhir orangtua (p value 0,02), dan penghasilan orangtua (p value 0,01) dengan pemanfaatan layanan kesehatan reproduksi remaja. Rekomendasi penelitian diharapkan perawat komunitas mampu meningkatkan cakupan kunjungan baik di sekolah maupun di keluarga dengan anak remaja agar remaja lebih terpapar informasi mengenai kesehatan reproduksi serta mampu memanfaatkan layanan kesehatan reproduksi yang tersedia secara optimal. Kata kunci: karakteristik; remaja; kesehatan reproduksi; pemanfaatan layanan reproduksi